PERUBAHAN HAK NORMATIF PEKERJA DALAM PEMUTUSAN HUBUNGAN KERJA BERDASARKAN UNDANG-UNDANG CIPTA KERJA - Hanny Jermias Onisimus Salamena; Moh. Saleh (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Abstract. The Omnibus Law on Job Creation (Law No. 11 of 2020) brought significant changes to labor regulations in Indonesia, particularly regarding termination of employment (PHK). This law provides greater flexibility for employers in the PHK procedure, especially for economic or efficiency reasons, but raises concerns about the protection of workers' rights, such as severance pay. In this context, Law No. 6 of 2023 was enacted to strengthen the protection of workers' normative rights, including in the PHK procedures and social security. This law clarifies the provisions related to PHK, offers better legal certainty, and strengthens sanctions for employers who violate the rules. Despite challenges in implementation, both laws aim to create a balanced labor climate that supports job creation and investment without sacrificing workers' rights.